Genetic analysis and phosphoinositide 3-kinase/protein kinase B signaling pathway status in ovarian endometrioid borderline tumor samples - Nakamura, Kohei (Oncol Lett, 2018)
Ovarian endometrioid borderline tumors (EBTs) are extremely rare, and are thought to be precursors of endometrioid carcinoma, beginning as adenofibroma or endometriosis and progressing in a slow, stepwise manner. In endometrioid carcinomas, a high frequency of activating mutations in phosphatase and tensin homolog (PTEN), β-catenin or AT-rich interaction domain 1A (ARID1A) genes, and the activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway have been observed. However, the frequency of these alterations in EBTs and how they contribute to tumor progression remain unclear. To the best of our knowledge, this is the first study to assess the status of the PI3K/AKT signaling pathway in EBTs, in association with PTEN and ARID1A mutations. PTEN mutations were observed in EBTs and also in the area of endometriosis without atypia. However, the PI3K/AKT signaling pathway was revealed to be activated only in EBTs. The observations of the present study suggest that the PTEN mutation represents an early event in EBT tumorigenesis, while additional genetic alterations may be necessary to activate the PI3K/AKT signaling pathway and induce the development of the invasive carcinoma.